ANALISIS KARAKTERISTIK FLUIDA MATA AIR PANAS DI DESA SAWANGAN KABUPATEN MINAHASA UTARA DENGAN MENGGUNAKAN GEOINDIKATOR Cl-Li-B - Poluakan, Willy Ch A.; Sompotan, Armstrong F.; Polii, Jeferson (LPPM Politeknik Saint Paul Sorong, 2025)
The need for energy in everyday life is very important, geothermal energy has the potential to become an energy source for power plants. Indonesia has one of the largest geothermal potentials, because Indonesia is located in the Ring of Fire. One of the provinces known for its abundance of geothermal energy is North Sulawesi. The purpose of this study is to determine the characteristics of this geothermal manifestation. The method used is the Cl-Li-B Geoindicator to determine the outflow zone or upflow zone of a geothermal system. The results of the study show that the manifestation has a temperature of 39â°C with a pH of 6.39 containing a higher chloride (Cl) content than Lithium (Li) and Boron (B), the chloride (Cl) content has a percentage of 82.3529% while for Lithium (Li) has a percentage of 11.7647% and Boron (B) has a percentage of 5.8823%. The data shows that of the three parameters studied, the relatively low B/Cl ratio indicates that the hot spring comes from an old geothermal reservoir and chloride (Cl) has the highest percentage of content, it can be concluded that this manifestation is in the outflow zone